Inheritance of a Share in a Limited Liability Company under Ukrainian Law - DIKOVSKA, Iryna A.; PRYTYKA, Iurii D. (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019, 2020)
The research focuses on one of the consequences of the death of the participant of a limited liability company under Ukrainian law: the emergence of a right to inherit his or her assets in the company. It analyses one of the most controversial issues of Ukrainian succession law: what types of assets the heirs inherit: the share in the authorized capital of the company or also the right to participate in it. As long as, on June 17, 2018, the Law of Ukraine ‘On Limited Liability and Additional Liability Companies’ has come into force, the research compares the approaches of previous legislation and the new Law. It has been concluded that the new Law makes the rule, under which the share in the authorized capital transfers to the heirs of the deceased participant, mandatory. It provides the automatic transfer of the right to participate in the company to the heirs. The new Law protects the interests of the heirs and does not take into account the interests of the other participants.